Targeting folded RNA: A branched peptide boronic acid that binds to a large surface area of HIV-1 RRE RNA() - Zhang, Wenyu (2013)
On-bead high throughput screening of a medium sized (1000–2000 Da) branched peptide boronic acid (BPBA) library consisting of 46,656 unique sequences against HIV-1 RRE RNA generated peptides with binding affinities in the low micromolar range. In particular, BPBA1 had a K(d) of 1.4 µM with RRE IIB, preference for RNA over DNA (27 fold), and selectivity of up to >75 fold against a panel of RRE IIB variants. Structure-activity studies suggest that the boronic acid moiety and “branching” in peptides are key structural features for efficient binding and selectivity for the folded RNA target. BPBA1 was efficiently taken up by HeLa and A2780 cells. RNA-footprinting studies revealed that the BPBA1 binding site encompasses a large surface area that spans both the upper stem as well as the internal loop regions of RRE IIB.